2016
DOI: 10.1038/srep39481
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble urokinase-type plasminogen activator receptor as a biological marker of bacterial infection in adults: a systematic review and meta-analysis

Abstract: The serum concentration of soluble urokinase-type plasminogen activator receptor (suPAR) reflects immune activation. We performed a meta-analysis to evaluate the usefulness of suPAR for the diagnosis and prognosis of bacterial infections. PubMed, Embase and Cochrane Library databases were searched for studies reporting the detection of suPAR in adult patients with bacterial infections. Seventeen studies were selected from 671 studies. The pooled sensitivity and specificity of suPAR for diagnosing infection wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 40 publications
3
38
1
7
Order By: Relevance
“…In critical illness and sepsis, serum levels of suPAR indicate an adverse prognosis, as consistently demonstrated in several cohort studies as well as a meta-analysis [4,5,[16][17][18]. However, suPAR has in the ICU setting a rather low accuracy in diagnosing sepsis [16,18,19].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In critical illness and sepsis, serum levels of suPAR indicate an adverse prognosis, as consistently demonstrated in several cohort studies as well as a meta-analysis [4,5,[16][17][18]. However, suPAR has in the ICU setting a rather low accuracy in diagnosing sepsis [16,18,19].…”
Section: Introductionmentioning
confidence: 87%
“…Despite the different etiologies and modes of injury, systemic inflammation, infections, and organ failure represent common determinants of outcome in ICU patients [1][2][3]. Circulating levels of the soluble plasminogen activation receptor (suPAR) are linked to inflammation, immune cell activation, and sepsis [4,5], supporting the concept that suPAR could be a universally applicable prognostic biomarker in the setting of emergency and intensive care medicine [6,7]. However, suPAR levels are also elevated in various clinical conditions including chronic kidney disease [8], liver cirrhosis [9], cardiac arrest [10], and HIV infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis study showed that high suPAR levels were associated with mortality in septic patients. 51 …”
Section: Discussionmentioning
confidence: 99%
“…Interest in suPAR rests mainly on the strong relationship between circulating levels of this compound and all-cause and CV mortality and other adverse clinical outcomes in patients with severe multiorgan diseases admitted into intensive care units, 9 , 10 in the general population, 11 as well as in patients with CV disease, 12 , 13 cancer, 11 sepsis, 28 and HIV. 29 In the present study, suPAR associated with all-cause, CV, and non-CV mortality in a dose-dependent fashion, and these associations held true both in diabetic and in nondiabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the production of suPAR from immature myeloid cells has been shown to be a constant source in focal and segmental glomerulosclerosis. 31 On binding its receptor, uPAR triggers the production plasmin as well as cell adhesion, migration, and proliferation, which are wide-ranging phenomena that participate in atherosclerosis, 32 infectious diseases, 28 and cancer. 11 , 33 …”
Section: Discussionmentioning
confidence: 99%